Activation of the mitogen‐activated protein kinase ERK1/2 signaling pathway suppresses the expression of ChREBPα and β in HepG2 cells. Issue 7 (17th June 2021) - Li, Lan; Sakiyama, Haruhiko; Eguchi, Hironobu; Yoshihara, Daisaku; Fujiwara, Noriko; Suzuki, Keiichiro
Abstract : The carbohydrate response element‐binding protein (ChREBP), a glucose‐responsive transcription factor that plays a critical role in the glucose‐mediated induction of genes involved in hepatic glycolysis and lipogenesis, exists as two isoforms: ChREBPα and ChREBPβ. However, the mechanism responsible for regulating the expression of both ChREBPα and β, as well as the mechanism that determines which specific isoform is more responsive to different stimuli, remains unclear. To address this issue, we compared the effects of several stimuli, including oxidative stress, on the mRNA and protein expression levels of ChREBPα and β in the hepatocyte cell line, HepG2. We found that H2 O2 stimulation suppressed the expression of both mRNA and protein in HepG2 cells, but the mRNA expression level of ChREBPβ was < 1% of that for ChREBPα levels. In addition, the reduction in both ChREBPα and β mRNA levels was reversed by PD98059, a selective and cell permeable inhibitor of the MEK/ERK pathway. Additionally, the administration of 12‐O‐tetradecanoylphorbol 13‐acetate (TPA) and staurosporine (STS), activators of extracellular‐signal‐regulated kinase (ERK) signaling, also resulted in a decrease in the levels of both ChREBPα and β mRNA in HepG2 cells through ERK signaling. These collective data suggest that oxidative stress, including STS treatment, suppresses the expression of ChREBPα and β via the activation of ERK signaling in HepG2 cells. Such a decrease in the levels of expression of ChREBPα and β could result in the suppression of hepatic glycolysis and lipogenesis, and this would be expected to prevent further oxidative stress. Abstract : The carbohydrate response element binding protein (ChREBP) is a glucose‐responsive transcription factor that strongly regulates glycolysis and lipogenesis. In this study, we showed that oxidative stress, including STS and TPA treatment, suppressed the expression of both ChREBPα and β through activation of ERK signaling in HepG2 cells.